Research Status on AC Stray - Current Interference of Buried Steel Pipeline - LI Xiao - long, WANG Zheng - xiao, LUO Yan - long, LI Chang - chun, HE Ren - yang (Cailiao Baohu, 2022)
With the rapid development of the energy, power distribution transmission and electrified rail transit systems of our country, the stray - current interference problem caused by the crossing and paralleling of buried steel pipelines and by the close laying distance has caught the attention of safety supervision departments and enterprises. Taking AC stray current as the object, the corrosion mechanism of buried steel pipelines under the interference of AC stray current was summarized and the characteristics of corrosion behavior under the influence of different factors was summarized. In addition, based on the different interference mechanisms, the current evaluation standards for the AC stray current interference was analysed, the problems of these standards were put forward and corresponding suggestions were proposed. In addition, the current technology and equipment for detecting and protecting against the stray current were analyzed and their advantages and limitations were studied. Finally, the focus and direction of the future research were pointed out.